Gambaran Keselamatan Pekerja Menggunakan Teknologi Pemantauan Drone pada Proyek Konstruksi PT. X Makassar - Muh Fathur Rahman MT Hardjo; Andi Wahyuni; Muhammad Rum Rahim (Hasanuddin Journal of Public Health, 2020)
Safety and Health of Construction work are activities to ensure and protect the safety and health of workers through accidents in the workplace. This study is to find out the description of the safety of workers using drone monitoring technology in construction activities at PT. X. This research is a type of descriptive research in a quantitative approach aimed to determine the safety of workers using drone monitoring technology in the construction project of PT. X Makassar 2020. The research will be conducted in November with a workforce of 108 people. The sample in this study was taken by purposive sampling technique so that the sample of 55 people. Data were collected using a questionnaire, Rapid Entry Body Assessment (REBA), analysis using SPSS software and drone. Data is presented in tabular form and narrated. This study shows the Knowledge variable at PT. X that out of 55 respondents (60%) respondents said that it was good. Based on the use of PPE, most respondents were classified as not compliant, namely as many as (67.3%), while the least were classified as compliant, as many as (32.7%). The most dominant work attitude of the respondents was Very High Risk Level (as much as 80%). While the least is the Medium Risk Level (3.6%). The results of the mapping in the rector's building, library and mosque using drones. The description of worker safety based on the variables of knowledge, PPE compliance, worker attitudes and hazards can be classified in part as good, but on variables.